Impacts of Peso Depreciation and Changes in Other Business and Economic Variables on Aggregate Output in Argentina (Global Journal of Management and Business Research, 2016)
This paper examines the effects of real depreciation of the Argentine peso and changes in other relevant macroeconomic variables on real GDP in Argentina. The results show that real GDP is negatively influenced by real depreciation of the peso, the real interest rate and the expected inflation rate and positively affected by the ratio of government spending or government deficit to GDP, the real stock price, the real oil price and U.S. real GDP. Therefore, recent depreciation of the peso hurts real GDP whereas recent rise in the stock price helps real GDP. Relatively high interest rates reduce real GDP through personal consumption spending, investment spending and net exports.
Keywords: real depreciation; interest rates; stock prices; oil prices; expected inflation rate